2019
DOI: 10.1101/601666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sortase-assembled pili promote extracellular electron transfer and iron acquisition inEnterococcus faecalisbiofilm

Abstract: 24Enterococcus faecalis is an opportunistic human pathogen and the cause of biofilm-25 associated infections of the heart, catheterized urinary tract, wounds, and the dysbiotic gut 26 where it can expand to high numbers upon microbiome perturbations. The E. faecalis sortase-27 assembled endocarditis and biofilm associated pilus (Ebp) is involved in adhesion and 28 biofilm formation in vitro and in vivo. Extracellular electron transfer (EET) also promotes E. 29 faecalis biofilm formation in iron-rich envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…The isolated mutants were investigated for their ability to transfer electrons generated in glucose catabolism to a graphite electrode depending on type of provided redox mediator. In parallel to our work, Lam et al (17) have studied properties of E. faecalis strains with transposon insertion in genes corresponding to those known to be important for ferric reductase activity in L. monocytogenes (13) and for DMK synthesis in E. faecalis. Although the approaches in our research groups were different and EET was not measured using the same type of The collected data for E. faecalis (this work and (17)) and L. monocytogenes (13) indicate that an atypical NADH dehydrogenase (Ndh3 in E. faecalis) with the FAD containing domain presumably on the cytoplasmic side of the membrane, EetA which is mainly exposed to the periplasm, and EetB in the membrane, are required for ferric reductase activity dependent on DMK.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The isolated mutants were investigated for their ability to transfer electrons generated in glucose catabolism to a graphite electrode depending on type of provided redox mediator. In parallel to our work, Lam et al (17) have studied properties of E. faecalis strains with transposon insertion in genes corresponding to those known to be important for ferric reductase activity in L. monocytogenes (13) and for DMK synthesis in E. faecalis. Although the approaches in our research groups were different and EET was not measured using the same type of The collected data for E. faecalis (this work and (17)) and L. monocytogenes (13) indicate that an atypical NADH dehydrogenase (Ndh3 in E. faecalis) with the FAD containing domain presumably on the cytoplasmic side of the membrane, EetA which is mainly exposed to the periplasm, and EetB in the membrane, are required for ferric reductase activity dependent on DMK.…”
Section: Discussionmentioning
confidence: 84%
“…These recent findings together prompted us to investigate to what extent EET to electrodes and ferric reductase activity are connected processes in E. faecalis. While our research work was in progress it was reported that EET to ferric iron in E. faecalis depends on genes corresponding to those in the gene cluster originally found in L. monocytogenes and on a gene encoding the tip adhesion protein EbpA (17). To identify proteins involved in EET to ferric ions and determine if these also are crucial for EET we have here screened a collection of mutants for ferric reductase deficiency, identified the responsible mutations, and analyzed bioelectrochemical properties of the mutants.…”
mentioning
confidence: 95%
“…Instead, increasing glycerol concentrations in the growth media enhanced biofilm formation in both the wild type control and mntE∷Tn mutant, regardless of Fe supplementation ( Figure S5 ). By contrast, these three glycerol catabolic genes ( glpF2, glpO, glpK ) were not upregulated under Mn supplemented conditions in wild type E. faecalis biofilm (Figure 4) and global transcriptional analysis showed that these genes are not Fe responsive in wild type OG1RF biofilm grown in Fe-supplemented media (38). Taken together, these results indicate that upregulation of glycerol catabolic genes is specifically observed in the absence of mntE when intracellular Fe levels are high and that glycerol supplementation contributes to biofilm growth.…”
Section: Resultsmentioning
confidence: 96%
“…Filaments of the type IV pili were also reported for some Gram-positive bacteria [86] . Although most of the functions of type IV pili in Gram-positive bacteria have been associated with mobility and adherence to host cells [86] , [87] , pili-like appendages have been observed in C. ferrireducens grown on iron oxides [74] , in Paenibacillus dendritiformis when growing on an electrode [28] and in E. faecalis pili revealed to contribute for EET [88] . It was demonstrated that E. faecalis biofilm matrix harboring iron sinks promotes EET and augments biofilm growth, increasing current generation in MFC [89] .…”
Section: Direct Electron Transfer In Gram-positive Bacteriamentioning
confidence: 99%
“…It was demonstrated that E. faecalis biofilm matrix harboring iron sinks promotes EET and augments biofilm growth, increasing current generation in MFC [89] . The biofilm associated pilus (Ebp) was demonstrated to be a key player in this process by sequestering iron in close proximity to the cells, either as surface attached pili or within the biofilm matrix, enabling E. faecalis to use it as terminal electron acceptor [88] .…”
Section: Direct Electron Transfer In Gram-positive Bacteriamentioning
confidence: 99%